The study and use of traditional knowledge in agroecological contexts - Carolina Alzate; Frédéric Mertens; Myriam Fillion; Aviram Rozin (Revista de la Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2019)
The importance of researching and maintaining traditional knowledge is a concern within contemporary academic debates and public policies. Scientist of different disciplines have recognized this importance, indicating this is a broader interdisciplinary issue. Specifically, within the field of agroecological science, the concept of traditional knowledge is basic to the analysis of agroecosystems. This essay aims to analyze, within scientific papers, the approaches to traditional knowledge through agroecological studies. First, insights from traditional knowledge studies in socio-ecological systems are presented as a wider view. Secondly, papers that illustrate agroecological approach to traditional knowledge and the usage of participative research methodologies are systematically reviewed to the forward development of five propositions: 1) traditional knowledge dynamics, 2) importance of traditional knowledge and professional’s ethics, 3) methodologies used for traditional knowledge gathering, 4) subjects of study in agroecological and traditional knowledge studies and 5) the integration of traditional knowledge with scientific knowledge.